Agrin Promotes Non-Small Cell Lung Cancer Progression and Stimulates Regulatory T Cells via Increasing IL-6 Secretion Through PI3K/AKT Pathway - Han, Linzhi; Shi, Hongjie; Ma, Shijing; Luo, Yuan; Sun, Wenjie; Li, Shuying; Zhang, Nannan; Jiang, Xueping; Gao, Yanping; Huang, Zhengrong; Xie, Conghua; Gong, Yan (Frontiers in Oncology, 2022)
Non-small cell lung cancer (NSCLC) has high mortality rates worldwide. Agrin contributes to immune synapse information and is involved in tumor metastasis. However, its roles in NSCLC and tumor immune microenvironment remain unclear. This study examined the effects and the underlying mechanisms of Agrin in NSCLC and tumor-infiltrated immune cells. Clinical tissue samples were used to confirm the bioinformatic predictions. NSCLC cells were used to investigate the effects of Agrin on cell cycle and proliferation, as well as invasion and migration. Tumor xenograft mouse model was used to confirm the effects of Agrin on NSCLC growth and tumor-infiltrated regulatory T cells (Tregs) in vivo. Agrin levels in NSCLC cells were closely related to tumor progression and metastasis, and its function was enriched in the PI3K/AKT pathway. In vitro assays demonstrated that Agrin knockdown suppressed NSCLC cell proliferation and metastasis, while PI3K/AKT activators reversed the inhibitory effects of Agrin deficiency on NSCLC cell behaviors. Agrin expression was negatively associated with immunotherapy responses in NSCLC patients. Agrin knockdown suppressed Tregs, as well as interleukin (IL)-6 expression and secretion, while PI3K/AKT activators and exogenous IL-6 rescued the inhibitory effects. In the mouse model, Agrin downregulation alleviated NSCLC cell growth and Treg infiltration in vivo. Our results indicated that Agrin promotes tumor cell growth and Treg infiltration via increasing IL-6 expression and secretion through PI3K/AKT pathway in NSCLC. Our studies suggested Agrin as a therapeutically potential target to increase the efficacy of immunotherapy in NSCLC patients.